2018
DOI: 10.3389/fenrg.2018.00054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Drought on Chemical Composition and Sugar Yields From Dilute-Acid Pretreatment and Enzymatic Hydrolysis of Miscanthus, a Tall Fescue Mixture, and Switchgrass

Abstract: Environmental factors like drought impact the quality of biomass entering a bioconversion process. Drought often reduces the sugar content in lignocellulosic biomass, which could have economic impacts, particularly when compounded with losses in dry biomass yield; however, the effects on conversion efficiency are not completely understood. This study investigated how drought may impact biomass composition and sugar yields from dilute-acid pretreatment and enzymatic hydrolysis of Miscanthus, a tall fescue mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 61 publications
(105 reference statements)
0
24
0
Order By: Relevance
“…It must also be considered how drought impacts the formation of certain degradation products that decrease conversion efficiencies though inhibition of enzymes during enzymatic hydrolysis and microorganisms during the fermentation step in a biochemical conversion process. For Miscanthus pretreated with dilute acid, enzymatic and fermentation inhibitors did not increase, however, this was likely a result of the dilute-acid pretreatment temperatures being lower than those required to form inhibitors [34]. In contrast, fermentation inhibitors were increased in drought stressed switchgrass in a study by Ong et al [32] where the switchgrass was Drought Impacts on Bioenergy Supply System Risk and Biomass Composition DOI: http://dx.doi.org/10.5772/intechopen.85295 chemically pretreated using ammonia fiber expansion (AFEX).…”
Section: Difference Between Percent Glucan (A) Xylan (B) and Ligninmentioning
confidence: 93%
See 4 more Smart Citations
“…It must also be considered how drought impacts the formation of certain degradation products that decrease conversion efficiencies though inhibition of enzymes during enzymatic hydrolysis and microorganisms during the fermentation step in a biochemical conversion process. For Miscanthus pretreated with dilute acid, enzymatic and fermentation inhibitors did not increase, however, this was likely a result of the dilute-acid pretreatment temperatures being lower than those required to form inhibitors [34]. In contrast, fermentation inhibitors were increased in drought stressed switchgrass in a study by Ong et al [32] where the switchgrass was Drought Impacts on Bioenergy Supply System Risk and Biomass Composition DOI: http://dx.doi.org/10.5772/intechopen.85295 chemically pretreated using ammonia fiber expansion (AFEX).…”
Section: Difference Between Percent Glucan (A) Xylan (B) and Ligninmentioning
confidence: 93%
“…Complicating reductions in crop yields, plants experience compositional changes during drought; increased extractive components, including soluble sugars, and decreased structural sugars were reported for important potential bioenergy crops like switchgrass, Miscanthus, mixed grasses, and corn stover [26,[32][33][34]. Studies have even observed reduced lignification in some cases possibly resulting from decreased plant growth as well as changes in lignin component distribution in plant cells impacting cell wall degradability [33][34][35]. These compositional changes can greatly impact yield of bioenergy conversion products from these biomass resources.…”
Section: Biomass Chemical Compositionmentioning
confidence: 99%
See 3 more Smart Citations